FRP composite materials strengthening of flat steel elements - Łagoda, Marek; Kowal, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article describes the study on the impact of FRP composite materials strengthening of flat steel slab. The influence of changing of bond end geometry on three point bending behavior of flat steel elements reinforced by CFRP patch has been investigated. A bond failure at steel-adhesive interface was a dominant failure mode. The test results showed clearly that geometry change of the bond end of strengthening CFRP plate and adhesive can significantly increase bond capacity. The use of reverse taper of CFRP patch with adhesive fillet tapes can improve the load capacity of the adhesive joint on the bending of the flat steel element reinforced by FRP patch. Conclusions and plan of further works on steel elements CFRP strengthening were described.